2019
DOI: 10.12659/ajcr.915006
|View full text |Cite
|
Sign up to set email alerts
|

Forme Fruste in Recurring Mid-Ventricular Variant of Takotsubo Cardiomyopathy

Abstract: Patient: Female, 69 Final Diagnosis: Mid ventricular type of Takotsubo cardiomyopathy Symptoms: Chest discomfort Medication: — Clinical Procedure: Angiography • 2D echocardiogram Specialty: Cardiology Objective: Unusual clinical course Background: Takotsubo cardiomyopathy (TC) is characterized as acute left ventricular dysfunction precipitated by intense emotional or physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…New electrocardiographic abnormalities, such as ST-segment elevation or elevation in cardiac troponin are observed. Reported recurrence rates range from 0 to 15% [4][5][6][7][8]. Although a few papers reported that the earliest time of recurrence was 8 days [4,6], in most cases, a relapse occurs within a few months or years [1,4,6,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…New electrocardiographic abnormalities, such as ST-segment elevation or elevation in cardiac troponin are observed. Reported recurrence rates range from 0 to 15% [4][5][6][7][8]. Although a few papers reported that the earliest time of recurrence was 8 days [4,6], in most cases, a relapse occurs within a few months or years [1,4,6,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%